Exploration of The Determining Factors of Attraction Situ Bagendit I Tourism Object Using Analytic Hierarchy Process (AHP) - Wati Susilawati; Athiya Noura; Dini Turipanam Alamanda; Syntia Apriani (International Journal of Artificial Intelligence Research, 2022)
This study aims to explore the determinants of the attractiveness of the Situ Bagendit I tourist attraction by using the analytic hierarchy process (AHP). This research uses mixed methods, exploratory type. The survey was conducted by observing and interviewing informants to obtain primary data. Further data by distributing questionnaires and analyzing the data using the analytic hierarchy process (AHP) technique. While secondary data or data obtained from articles, textbooks, research, online news, and articles on websites and other sources. Data analysis using Expert Choice technique based on Analytic Hierarchy Process (AHP) and data verification using triangulation. The findings show that based on the results of the highest assessment criteria, namely ease of access (0.463), exciting attractions (0.398), and modern facilities (0.139). As an alternative factor, equestrian tourism (0.206) is an important part of the attraction of Situ Bagendit I attractions, while parks (0.196), tracking tours (0.188), amphitheater shows (0.153), children's playgrounds (0.133), and water tourism ( 0.124) becomes a supporting role in increasing the attractiveness of the Situ Bagendit I tourist attraction. It can be concluded that equestrian tourism is an attractive factor for the Situ Bagendit I tourist attraction where tourists can travel and see the view around the tourist attraction while riding.